Oxford reading tree : level 4 : floppy's phonics : sounds and letters : . Book 22 - Hepplewhite, Debbie; Hunt, Roderick ([S.l.] : Oxford University Press, 2011)
There are 6 books at Level 4: Book 19 'Revise and Blend' Book 20 'Revise and Blend' Book 21 practises 'ay, oy, ea, ie' Book 22 practises 'ow, ew, ew, ou' Book 23 practises 'ir, aw, eer, are' Book 24 practises 'ce, ea, o, ed' Each sound/alternative spelling is explored through an Oxford Reading Tree scene, first the children should read the decodable word lists, before trying to find the words within the picture. Consolidation activities include spelling activities and reading short texts. There are a total of 42 books in this series from Level 1 to Level 5 (Letters and Sounds Phase 1 to Phase 5)